Nano–electron volt Fourier-limited transition of a single surface-adsorbed molecule - Masoud Mirzaei; Alexey Shkarin; Burak Gurlek; Johannes Zirkelbach; Ashley J. Shin; Irena Deperasińska; Boleslaw Kozankiewicz; Tobias Utikal; Stephan Götzinger; Vahid Sandoghdar (Science, 2026)
High-resolution spectroscopy allows the probing of weak interactions and subtle phenomena. Although such measurements are routinely performed in the gas phase and in crystalline materials, studies of adsorbed species on surfaces have previously fallen short of the ultimate spectral resolution, where dephasing is eliminated and the transition linewidth is determined by the excited-state lifetime. In this work, we devise an approach to surface preparation and deposition that provides access to Fourier-limited electronic transitions in single molecules on the surface of an organic crystal. By performing spectroscopy and super-resolution microscopy at liquid helium temperature, we shed light on the spectral and spatial features of the adsorbed species. Our results pave the way for investigations in solid-state physics, where angstrom spatial resolution can be combined with high-resolution laser spectroscopy.